Report of the Secretary-General of the Commonwealth of Independent States Sergey Lebedev on the topic: "On the Chairmanship of the Russian Federation in the Commonwealth of Independent States in 2024" - S. N. Lebedev (Евразийская интеграция: экономика, право, политика, 2024)
.